2009
DOI: 10.1128/mcb.00465-09
|View full text |Cite
|
Sign up to set email alerts
|

Mechanoregulation of Proliferation

Abstract: The proliferation of all nontransformed adherent cells is dependent upon the development of mechanical tension within the cell; however, little is known about the mechanisms by which signals regulated by mechanical tension are integrated with those regulated by growth factors. We show here that Skp2, a component of a ubiquitin ligase complex that mediates the degradation of several proteins that inhibit proliferation, is upregulated when increased mechanical tension develops in intact smooth muscle and that it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Beller et al (2008) found that the aortic root displacement increases the longitudinal stress in the AA at the outer curvature, which can explain the preferential axial VSMC orientation at this location. In addition, we found an increased VSMC density at the outer curvature, which again supports the hypothesis of a remodeling response to increased strain/stress, which has been shown to regulate the VSMC proliferation (Jiang et al, 2009).…”
Section: Discussionsupporting
confidence: 70%
“…Beller et al (2008) found that the aortic root displacement increases the longitudinal stress in the AA at the outer curvature, which can explain the preferential axial VSMC orientation at this location. In addition, we found an increased VSMC density at the outer curvature, which again supports the hypothesis of a remodeling response to increased strain/stress, which has been shown to regulate the VSMC proliferation (Jiang et al, 2009).…”
Section: Discussionsupporting
confidence: 70%
“…Interestingly, we observed that this control acts on a timescale similar to that of Yes-associated protein (YAP) inactivation after inhibition of cytoskeletal tension (35,38). Cytoskeletal tension therefore might serve as a mechanical read-out for spatial constraints to cell size and might be transduced to known regulators of growth, such as YAP, Skp2, or ERK (34,35,(38)(39)(40)(41)(42)(43). Although this system is faster than an average cell cycle, the 8-h delay in the proliferative response, together with the hysteresis-free adaption, would ensure that open space has to be available for a significant time to trigger an invasive response in a growing tissue and would prevent tissues from up-regulating cell proliferation in response to short-lived changes in their mechanical environment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies in vivo have provided evidence that such a mechanism might control cell proliferation in tissue development and disease (39,(44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently become recognized that Skp2 acts as a node governing the integration of signals from mechanical tension and growth factors to regulate cell proliferation (66). Such tension-related integration of signaling through Skp2 can impact fibrosis, which was demonstrated by therapeutic delivery of Skp2-targeting siRNAs to provide protection against fibrosis and reduce scarring in a glaucoma filtration surgery model (67).…”
Section: Discussionmentioning
confidence: 99%